Associated dental anomalies: case report Múltiplas anomalias dentárias associadas: caso clínico - Daniela Gamba Garib; Nildiceli Leite Melo Zanella; Sheldon Peck (University of São Paulo, 2005)
Certain human dental anomalies frequently occur together, supporting the accumulated evidence of the shared genetic control of dental developmental disturbances. The present study reports a rare and interesting case of a 12-year-old girl with an association of multiple dental abnormalities, including agenesis, tooth malposition and delayed development. The etiology and treatment planning are discussed with reference to the literature. The clinical implications of genetically controlled patterns of dental anomalies are important in the establishment of early diagnosis and appropriate orthodontic intervention. Certas anomalias dentárias humanas freqüentemente ocorrem concomitantemente, contribuindo para validar as evidências do controle genético nos distúrbios de desenvolvimento. O presente estudo relata um caso raro e interessante de uma jovem de 12 anos de idade, com associação de anormalidades dentárias múltiplas, incluindo agenesia, ectopia e atraso no desenvolvimento dentário. A etiologia e tratamento planejados são discutidos com referência à literatura. As implicações clínicas do padrão de anomalias dentárias geneticamente controladas são importantes no estabelecimento do diagnóstico precoce e de adequada intervenção ortodôntica.